Reasons for switching the primary health providers among national health insurance participants in Klungkung District, Bali Province, Indonesia - Windu, I Kadek; I Ketut Suarjana; I Nyoman Sutarsa (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: National Health Insurance Provider (BPJS Kesehatan) facilitates the distribution of National Health Insurance (NHI) participants. High number of 1,947 NHI participants were switched primary health providers in Klungkung, Bali between July to December 2021.This study aims to explore the reasons for the switching of providers among NHI participants and the health providers’ efforts to minimize it. Methods: A qualitative descriptive study guided by an access theory was conducted in Klungkung District between December 2022 to March 2023. A total of 18 informants were purposively recruited, consisting of NHI participants (12 people), health service providers (4 people), BPJS Kesehatan (1 person) and staff of the district health office (1 person). Data was collected through in-depth interviews guided by interview guidelines. Data were analyzed using a thematic approach and presented in a descriptive narrative. Results: NHI participants in Klungkung District switched provider due to spatial and non-spatial reasons. Spatial reason was the distance and time to the health provider. Non-spatial reasons included (1) conflict in social relations due to service and negative attitudes of health workers, (2) economic considerations in the health system which are difficult to reach, and (3) external encouragement. Strategies that have been or can be implemented to minimize the switching of PHCs were adjusting operational hours, improving the infrastructures, administration through fulfilling accreditation, service quality and training for human resources. Conclusion: The dominant reason for switching of PHCs is associated with negative social interaction experiences related to human resources and service facilities at PHCs. PHCs are expected to be able to improve the quality of services through improving human resources and service delivery facilities.